Analisis Pewarisan Keilmuan Ulama Madura Terhadap Penyebaran Hadis Musalsal - Arifah, Afro' Anzali Nurizzati; Rochmawati , Ida (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
Madurese ulama are role models or local leaders for the Madurese community so they have a big influence on the development of religious scholarship in Madura, especially in the field of Hadith. Not many Indonesian hadith scholars have visited the Madura region, so the Madurese people are quite far from teaching the hadith of the Prophet SAW. This is what then caused Madurese scholars to write hadith books and distribute them to all corners of Madura. This hadith book contains musalsal hadiths that Madurese scholars obtained from their teachers through several conditions in the process of narrating musalsal hadiths. The existence of Madurese ulama and their hadith books created the hadiths of the Prophet SAW. well maintained in Madurese society.  This research aims to see the role of Madurese ulama in preserving the Musalsal hadith and the extent to which the Musalsal hadith book has become a reference in the Madura region. The research method used in this research is qualitative with the type of library research. In addition, this research uses R.G.A.'s knowledge transmission theory. Dolby explains the process of transferring and conveying knowledge from one party to another, whether using an object as a result or not. The results of this research provide evidence that the role of Madurese ulama is very important in the process of preserving the Musalsal hadith and the extent to which the Musalsal hadith book has become a reference for knowledge in Madura.